(untitled) (Research, Society and Development, 2022)
Objective: to analyze the stress level and identify the most stressful factors for adolescent parents of newborns admitted to a Neonatal Intensive Care Unit (NICU). Method: quantitative and cross-sectional study, with adolescent mothers/fathers of newborns admitted to the NICU, aged between 10 and 19 years, from May to October 2021. For data collection, the Brazilian version of the Parental Stress Scale: Neonatal Intensive Care Unit (PSS: NICU) was used. The analysis was performed using the SPSS Statistics software, with measures of central tendency and dispersion. Results: the survey had nine participants, the subscale “Change in the role as mother/father” presented the highest stress level (mean=3,85), followed by “Baby’s appearance and behavior” (mean=2,63) and “Images and sounds” (mean=1,82). Conclusion: the inclusion of parents in the care of the child in the Neonatal Intensive Care Unit is a practice that should be encouraged, as it will strengthen the bond and alleviate the stress experienced during hospitalization.